Correlating pore size and shape to local disorder in microporous carbon: A combined small angle neutron and X-ray scattering study. (October 2017) - Jafta, Charl J.; Petzold, Albrecht; Risse, Sebastian; Clemens, Daniel; Wallacher, Dirk; Goerigk, Günter; Ballauff, Matthias
Abstract: We present a model free analysis of the structure of a microporous carbon (Kynol fiber cloth) with neutrons (SANS) and X-rays (SAXS). SANS with contrast matching is used to analyze the accessible pores. It is shown that the SAXS- and the SANS-intensities agree after correction of the SANS specific background. Moreover, we analyze the scattering contribution due to the finite size and the bending of the carbon sheets. This contribution that scales with q −2 at high q -values ( q : magnitude of scattering vector) is subtracted and the remaining intensity that exhibits a q −4 final slope gives the specific inner surface (1090 m 2 /g) and the porosity (29%) with excellent precision. The spatial distribution of the pores is analyzed in terms of the chord length distribution g(r). This distribution has its maximum below 1 nm and a finite intercept g(0) that indicates pores with sharp edges. The analysis gives furthermore the number and weight-average chord length. Finally, a parameter characterizing the degree of disorder of the carbonaceous structure introduced by Ruland was determined. Its value (25%) indicates a rather disordered structure that is visualized in terms of a detailed model. The entire analysis shows the power of small-angle scattering for a detailed analysis of microporous structures. Graphical abstract: